Evaluation of the effects of the performance-based bonus incentive scheme - Jose Ramon G. Albert; Ronald U. Mendoza; Janet S. Cuenca; Jana Flor V. Vizmanos; Mika S. Mu\~noz (Philippine Institute for Development Studies (PIDS), 2020)
In 2012, the government established a Performance-Based Bonus (PBB) scheme to reward performance, align individual personnel and team-level efforts with agency-wide targets, and improve public service delivery in the Executive Department. The Department of Budget and Management, together with other oversight agencies and the Development Academy of the Philippines, manage the implementation of the PBB using the framework of the Results-Based Performance Management System. They deem it critical to study the effect of the PBB on government efforts to boost productivity and push reforms, as well as government employees' individual and team-level motivations and productivity, especially given the budgetary implications of the incentive scheme. Prior to this study, a process evaluation of the PBB was conducted to clarify whether and to what extent the PBB worked as planned. This follow-up study examines the possible impact of the PBB by employing mixed methods research drawing on primary and secondary data, undertaking not only a perception-based survey on effects of the PBB on over 1,200 respondents, but also seven focus group discussions with PBB focal points and members of the performance management teams of selected agencies, as well as representatives of oversight agencies. The findings suggest while the PBB has had some design issues and implementation challenges (e.g. changes in eligibility requirements across the years, gaming and dysfunctional behavior), the PBB is generally welcomed across the bureaucracy. Further, there is evidence that the PBB has contributed to boosting individual, team-level and agency-wide improvements in motivation and productivity. Results of the study suggest that PBB could be further re-designed to sharpen its effects on public sector reform.
Keywords: 330; performance-based bonus; public sector performance; productivity; motivation Results-Based Performance Management